Sosialisasi Pencegahan Bahaya Stunting dan Dampaknya di Desa Semadam Awal Kecamatan Semadam Kabupaten Aceh Tenggara - Arpina Fajarnita; Devi Susanti; Herlitawati Herlitawati; Rohani Rohani (jurnal ABDIMAS Indonesia, 2024)
Stunting is a major nutritional problem faced by Indonesia. According to Nutritional Status Monitoring (PSG) data for the past three years, the prevalence of stunting in toddlers has increased from 27.5% in 2016 to 29.6% in 2017. The incidence of stunting has increased. The results of a survey in Semadam District, Southeast Aceh Regency found that during the new normal period of Covid-19, Posyandu activities held in each village followed the Covid-19 health protocol. Each village has 3 to 5 Posyandu cadres who are tasked with assisting Posyandu activities for toddlers. Semadam District is one of the stunting locus villages that receives stunting education. So it is important for the community to be provided with supplies on the importance of preventing stunting and its impact on toddlers in Semadam Village. The mandatory output targets achieved are publications in national journals with EISSN, publications in electronic mass media, activity videos uploaded on YouTube and increasing knowledge and skills of partners.